2013
DOI: 10.1523/jneurosci.0180-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Cortex Activation Causes Rapid Plasticity of Auditory Cortical Processing

Abstract: Neurons in the primary auditory cortex (A1) can show rapid changes in receptive fields when animals are engaged in sound detection and discrimination tasks. The source of a signal to A1 that triggers these changes is suspected to be in frontal cortical areas. How or whether activity in frontal areas can influence activity and sensory processing in A1 and the detailed changes occurring in A1 on the level of single neurons and in neuronal populations remain uncertain. Using electrophysiological techniques in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 53 publications
16
62
0
Order By: Relevance
“…A commonly used procedure to assess the magnitude of top-down mechanisms is to compare neural responsiveness during two different states of behavioral engagement (37,(44)(45)(46)(47)(48)(49). Specifically, top-down inputs are thought to actively modulate ACx responses during task performance (or "engagement") but not during nontask ("disengaged") listening sessions (50,51). Thus, the difference between engaged and disengaged sensitivity is a proxy for the strength of a top-down mechanism.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…A commonly used procedure to assess the magnitude of top-down mechanisms is to compare neural responsiveness during two different states of behavioral engagement (37,(44)(45)(46)(47)(48)(49). Specifically, top-down inputs are thought to actively modulate ACx responses during task performance (or "engagement") but not during nontask ("disengaged") listening sessions (50,51). Thus, the difference between engaged and disengaged sensitivity is a proxy for the strength of a top-down mechanism.…”
Section: Significancementioning
confidence: 99%
“…For our purposes, top-down refers to the functional influence of a higher-order brain region on neural activity in ACx, brought about by task engagement. Several plausible candidate regions may mediate this top-down effect, either in isolation or in concert with one another, including frontal cortex (50,51), nucleus basalis (73)(74)(75), locus coeruleus (76), ventral tegmental area (77,78), and multisensory cortex (17).…”
Section: Significancementioning
confidence: 99%
“…(a ) Tonotopic best frequency (BF) map reconstructed from ~50 extracellular multiunit recording sites from the middle layers of mouse AI, each spaced ~100 μm apart (data from [18]) In addition to receiving heavy feedforward sensory input from the medial geniculate body, AI tonotopic organization is influenced by long-range neuromodulatory inputs such as dopaminergic (DA) inputs from the ventral tegmental area [141], noradrenergic (NA) inputs from locus coeruleus [142], serotinergic inputs from the dorsal raphe (5-HT) [143], glutamatergic inputs from the frontal cortex [144], and cholinergic (ACh) input from nucleus basalis [49]. Of these systems, retuning of auditory response properties by cholingeric modulation is by far the best understood.…”
Section: Figurementioning
confidence: 99%
“…First, this result provides insight into the functional role of structural connections between the OFC and superior temporal gyrus previously reported in monkeys (Barbas et al, 1999; Petrides & Pandya, 2007). Another study in mice also showed OFC stimulation modulates sensory-evoked activity in the primary auditory cortex (Winkowski, Bandyopadhyay, Shamma, & Kanold, 2013). These studies converge on the OFC’s capacity for top-down sensory modulation of the auditory cortex across species.…”
mentioning
confidence: 96%